H₂S Gas Sensor Based on Ru-MoO₃ Nanoflake Thick Film - Ungkana Inpan (2018)
In this study, H₂S-sensing characteristics of the spincoated ruthenium loaded molybdenum trioxide nanoflake (Ru-MoO₃ NFs) thick films with 0-1.00 wt% Ru concentrations have been studied. The morphologies, cross section and elemental compositions of sensing films were characterized by SEM and EDS line-scan analyses. The influence of Ru concentration on H₂S response of the thick film sensor was studied at the operating temperatures ranging from 200 to 350 °C. It was found that 0.5 wt% RuMoO₃ film exhibited an enhanced response of ~30 to 10 ppm H₂S, which was more than one order of magnitude higher than that of unloaded one. Plausible mechanisms responsible for the enhanced H₂S response by sensing films of Ru-MoO₃ NFs were discussed on the basis of the catalytic spill-over effects and enhanced specific surface area provided by Ru nanoparticles.